Accuracy of Wayne’s criteria in diagnosing hyperthyroidism: a prospective study in south Kerala, India - S., Naraintran; David S., Sandeep Kumar; K., Raveendran; B. K., Eashwara Pillai (International Surgery Journal, 2018)
Background: Thyroid is an important endocrine gland regulating the metabolism of body from utero to maturation. Thyroid related diseases are most common among all endocrine diseases. Hyperthyroidism causes major metabolic derangement and hence the need for a screening test to diagnose the disease holds greater public health importance in a populated country like India. The study aims at finding the sensitivity of Wayne’s Criteria in correlation with Biochemical analysis in screening Hyperthyroidism. Methods: A prospective study done to screen patients with symptoms suggestive of hyperthyroidism coming to surgery department of Dr. S. M. C. S. I. medical college over a period of one year from September 2016 to September 2017 with the aid of Wayne’s Diagnostic criteria and biochemical analysis. Results: Of the total 53 cases studied, 23 cases were biochemically hyperthyroid. of the 23 cases Wayne’s criteria identified 20 cases as hyperthyroid, 2 cases were Disambigous and 1 was diagnosed as Euthyroid. Of the 30 biochemically Euthyroid patients Wayne’s criteria picked up 27 true Euthyroid patients, 2 patients as Disambigous and 1 patient was falsely diagnosed as Hyperthyroid. Sensitivity of the criteria was found to be 86.9%, specificity as 96%, positive predictive value was 95.2% and Negative predictive value was 90%. Conclusions: Wayne’s criteria holds a good deal of diagnostic accuracy. With high sensitivity specificity Wayne’s criteria can be applied as a screening test to diagnose a hyperthyroidism for early diagnosis and referral at the primary health care level in a populated country.